Valorisation of agricultural waste derived biochars in aquaculture to remove organic micropollutants from water – experimental study and molecular dynamics simulations. (15th December 2021) - Mrozik, Wojciech; Minofar, Babak; Thongsamer, Thunchanok; Wiriyaphong, Nathacha; Khawkomol, Sasiwimol; Plaimart, Jidapa; Vakros, John; Karapanagioti, Hrissi; Vinitnantharat, Soydoa; Werner, David
Abstract: In this work, we evaluated the valorisation of agricultural waste materials by transforming coconut husks and shells, corncobs and rice straw into biochar for water treatment in aquaculture. We compared the biochars' suitability for removal of organic micropollutants (acetaminophen, oxytetracycline, tetracycline, enrofloxacin, atrazine, diuron and diclofenac) from surface water needed for aquaculture. The biochars were prepared by three methods ranging from inexpensive drum kilns (200 °C) to pyrolysis with biogasfication (350–750 °C). Overall, antibiotics tetracycline and enrofloxacin were the most strongly sorbed micropollutants, and coconut husk biochar prepared at 750 °C was the best sorbent material. Molecular Dynamics simulations indicated that the major sorption mechanism is via π-π stacking interactions and there is a possibility of multilayer sorption for some of the micropollutants. We observed, a strong impact of ionic strength (salinity), which is an important consideration in coastal aquaculture applications. High salinity decreased the sorption for antibiotics oxytetracycline, tetracycline and enrofloxacin but increased diclofenac, atrazine and diuron sorption. We considered coconut husk biochar produced in drum kilns the most practical option for biochar applications in small-scale coastal aquacultures in South Asia. Pilot trials of canal water filtration at an aquaculture farm revealed that micropollutant sorption by coconut husk biochar under real-world conditions might be 10–500 times less than observed in the laboratory studies. Even so, biochar amendment of sand enhanced the micropollutant retention, which may facilitate subsequent biodegradation and improve the quality of brackish surface water used for food production in coastal aquaculture. Graphical abstract: Image 1 Highlights: Biochars (BCs) derived from agricultural waste were evaluated for water treatment. Four wastes, three pyrolysis methods and seven micropollutants were investigated. Coconut husk BC pyrolysed at 750 °C was the best micropollutant sorbent. Molecular dynamics simulations indicated that the major sorption mechanism is via π-π stacking interactions. BC amendment benefits in water filtration were demonstrated for field conditions.